Experimental Study on Variable-Amplitude Fatigue of Welded Cross Plate-Hollow Sphere Joints in Grid Structures - Jin-Feng Jiao; Hong-Gang Lei; Y. Frank Chen (Advances in Materials Science and Engineering)
The fatigue stress amplitude of the welded cross plate-hollow sphere joint (WCPHSJ) in a grid structure varies due to the random loading produced by suspending cranes. A total of 14 specimens considering three different types of WCPHSJs were prepared and tested using a specially designed test rig. Four typical loading conditions, “low-high,” “high-low,” “low-high-low,” and “high-low-high,” were first considered in the tests to investigate the fatigue behavior under variable load amplitudes, followed by metallographic analyses. The experimental and metallographic analysis results provide a fundamental understanding on the fatigue fracture form and fatigue mechanism of WCPHSJs. Based on the available data from constant-amplitude fatigue tests, the variable-amplitude fatigue life of the three types of WCPHSJs was estimated using the Miner rule and Corten-Dolan theory. Since both accumulative damage theories yield virtually same damaging results, the Miner rule is hence suggested to estimate the fatigue life of WCPHSJs.